2013
DOI: 10.1371/journal.pone.0062059
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ambient Temperature and Acute Myocardial Infarction Hospitalisations in Gothenburg, Sweden: 1985–2010

Abstract: Cardiovascular disease (CVD) is the number one cause of death globally and evidence is steadily increasing on the role of non-traditional risk factors such as meteorology and air pollution. Nevertheless, many research gaps remain, such as the association between these non-traditional risk factors and subtypes of CVD, such as acute myocardial infarction (AMI). The objective of this study was to investigate the association between daily ambient temperature and AMI hospitalisations using a case-crossover design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…In Tibet, living at extreme altitude places special strains on the cardiovascular system (Wu and Miao, 2002;Wu et al, 2007) and the typical high-fat, low-fiber Tibetan diet also contributes to high rates of heart diseases, stroke and obesity Yan et al, 2001;Yang et al, 2008;Zheng et al, 2011). Future research may investigate whether temperature-related risk of cardiovascular diseases varies by specific disease category, such as stroke and acute myocardial infarction (Wichmann et al, 2013). In the county with the most extreme weather, we found those dying outside a hospital were more susceptible to cumulative cold effects.…”
Section: Cold Effectsmentioning
confidence: 81%
See 1 more Smart Citation
“…In Tibet, living at extreme altitude places special strains on the cardiovascular system (Wu and Miao, 2002;Wu et al, 2007) and the typical high-fat, low-fiber Tibetan diet also contributes to high rates of heart diseases, stroke and obesity Yan et al, 2001;Yang et al, 2008;Zheng et al, 2011). Future research may investigate whether temperature-related risk of cardiovascular diseases varies by specific disease category, such as stroke and acute myocardial infarction (Wichmann et al, 2013). In the county with the most extreme weather, we found those dying outside a hospital were more susceptible to cumulative cold effects.…”
Section: Cold Effectsmentioning
confidence: 81%
“…Cardiovascular diseases are the number one cause of death globally and also in China. Evidence is mounting weather changes (e.g., variations in temperature) influence cardiovascular mortality and morbidity (Atsumi et al, 2013;Khanjani and Bahrampour, 2013;Madrigano et al, 2013;Wichmann et al, 2013;Zeng et al, 2012). Some studies found that those dying outside a hospital were more vulnerable to extreme cold (O'Neill et al, 2003) and heat (Medina-Ramón et al, 2006) than individuals who died in-hospital.…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining and reading full texts of the remaining articles, 34 studies were excluded: 4 had not sufficient data, 4 were the same or overlapping dataset, 12 were long-term exposure analysis, 5 were reviews or meta-analysis, 7 did not explore the effect of PM2.5 or PM10, and 2 were reported in nonEnglish language. Then, reviewing of reference lists of all the identified articles, related published reviews, metaanalysis, and excluding studies with the same or overlapping dataset in the same region, finally, 31 studies were included (Medina et al 1997;Hoek et al 2000;Linn et al 2000;Mann et al 2002;Sharovsky et al 2004;Peters et al 2005;Sullivan et al 2005;Zanobetti and Schwartz 2005;Barnett et al 2006;Cendon et al 2006;Lanki et al 2006;Pope et al 2006;Zanobetti and Schwartz 2006;Cheng et al 2009;Stieb et al 2009;Ueda et al 2009;Zanobetti and Schwartz 2009;Belleudi et al 2010;Hsieh et al 2010;Mate et al 2010;Rich et al 2010;Nuvolone et al 2011;von Klot et al 2011;Chang et al 2013;Rosenthal et al 2013;Wichmann et al 2013;Bard et al 2014;Milojevic et al 2014;Talbott et al 2014;Wichmann et al 2014;Xie et al 2014). The study screening process is presented briefly in Fig.…”
Section: Identification and Characteristics Of Included Studymentioning
confidence: 99%
“…There are very few studies focused only on one [9] or several specific cardiovascular health outcomes [10]. According to this type of research, some authors found that while few categories of the CVD, like acute myocardial infarction (AMI) and congestive heart failure, increased with maximum temperature, the other CVD (coronary atherosclerosis and pulmonary heart diseases) significantly decreased with temperature [11].…”
Section: Introductionmentioning
confidence: 99%